Determinación del valor de la energía metabolizable de harina de soya a través de pruebas de digestibilidad in vivo en gallos reproductores adultos. - Rodríguez Arévalo, Andrés Francisco (2023)
Poultry farming aimed at raising reproductive males has high importance in the economic sectors of Ecuador; in turn, the need to cover the metabolizable energy requirements in their diet is high. The objective of the study was to determine the value of metabolizable energy of soybean meal through in vivo digestibility tests in adult breeding roosters. The research was carried out in the province of Chimborazo, working with adult breeding roosters, two treatments were established (T1 = 32% and T2 = 42% of protein contained in the diet with soy flour), and seven repetitions, the roosters were located and managed in metabolic exclusion cages, the study variables were; i) hygroscopic humidity, ii) ash, iii) crude protein, iv) ethereal extract, v) crude fiber, vi) nitrogen-free extract, vii) apparent and true metabolizable energy, the data obtained were analyzed by means of the Fisher and Tukey. Regarding the results obtained when evaluating the concentrations of humidity, fiber, crude protein and nitrogen-free extract, T2 presented the best results, while in the ethereal extract variable, T1 stood out with its content of 40.6%, compared to T2, regarding the dry matter digestibility coefficient (77.92%); crude fiber (87.27%); organic matter (8059%); digestibility of the nitrogen-free extract (72.9%), the best results were provided by T2, finally, it was determined that the best true metabolizable energy content was generated by T2 (2005.31 Kcal/Kg M.S).